3D Architectured Anodes for Lithium‐Ion Microbatteries with Large Areal Capacity. Issue 4 (6th April 2014) - Cirigliano, Nicolas; Sun, Guangyi; Membreno, Daniel; Malati, Peter; Kim, C. J.; Dunn, Bruce
Abstract Progress in the miniaturization of batteries has lagged well behind that of microelectronics. Although lithium‐ion (Li‐ion) battery technology has been vital in advancing portable consumer electronics, it is not clear whether future generations of microscale devices can be powered using traditional battery designs. In this paper, we report on the fabrication and properties of battery electrodes comprised of arrays of vertically aligned carbon rods. The electrodes exhibit good reversibility and represent the first carbon arrays to achieve areal capacities greater than 5 mAh cm−2 at relatively large current densities, although the capacity does fade with cycling. The 3D battery designs based on these architectures offer the promise of achieving high energy densities within small footprint areas.